2014
DOI: 10.1016/j.jcyt.2013.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of advanced therapy medicinal products in Europe and the role of academia

Abstract: GMP facilities successfully developing ATMPs are present in all MS. However, the implementation of regulations is heterogeneous between MS, with substantial differences in the definition of ATMPs and in the approved manufacturing environment. The cost of GMP compliance is underestimated by research funding bodies. This is detrimental to development of new ATMPs and commercialization of any that are successful in early clinical trials. Academic GMP practitioners should strengthen their political visibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 4 publications
(3 reference statements)
0
63
0
1
Order By: Relevance
“…QPs are approved by the regulatory authority and often have a pharmaceutical background. An issue identified by Pearce et al [22] and also observed by us [57] is the hesitation of QPs to take over responsibility for releasing an ATMP, as such products may not be part of their area of expertise. While we are in the comfortable situation that denovoDerm and denovoSkin products are manufactured in a certified GMP facility in Zurich [58] including release by a QP, difficulties were encountered when arranging import of the ATMPs to The Netherlands for an international multicenter clinical trial.…”
Section: Hurdles To Clinically Apply Atmps In Europementioning
confidence: 95%
See 3 more Smart Citations
“…QPs are approved by the regulatory authority and often have a pharmaceutical background. An issue identified by Pearce et al [22] and also observed by us [57] is the hesitation of QPs to take over responsibility for releasing an ATMP, as such products may not be part of their area of expertise. While we are in the comfortable situation that denovoDerm and denovoSkin products are manufactured in a certified GMP facility in Zurich [58] including release by a QP, difficulties were encountered when arranging import of the ATMPs to The Netherlands for an international multicenter clinical trial.…”
Section: Hurdles To Clinically Apply Atmps In Europementioning
confidence: 95%
“…Interestingly, a survey at European research centers working with ATMPs showed that most of the participating centers supported strict and careful ATMP regulation. None of the centers in this survey supported potential lower GMP standards for ATMPs than standard medicines or lower standards for academic groups [22]. …”
Section: Advanced Therapy Medicinal Products (Atmps)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, high operational expenditures for such facilities need to be taken into account [86]. Marketing of such ‘advanced medicinal products', is a complex process which in Europe is overseen by the European Medicines Agency [85,88]. Hence, practicability and cost factors pose limits to the implementation of such new types of personalized medicines in blood centers.…”
Section: Nk-92 - a Third-party Nk Cell Drugmentioning
confidence: 99%